2015
DOI: 10.1155/2015/621845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unilateral Cochlear Implantation on Balance Control and Sensory Organization in Adult Patients with Profound Hearing Loss

Abstract: Many studies were interested in the consequence of vestibular dysfunction related to cochlear implantation on balance control. This pilot study aimed to assess the effects of unilateral cochlear implantation on the modalities of balance control and sensorimotor strategies. Posturographic and vestibular evaluations were performed in 10 patients (55 ± 20 years) with profound hearing loss who were candidates to undergo unilateral multichannel cochlear implantation. The evaluation was carried out shortly before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
4
28
0
1
Order By: Relevance
“…In contrast, those who would have been considered to be likely to have balance problems (those over 60 years of age and those with a balance deficit preoperatively) had no significant worsening in balance control, possibly because central compensation processes for the prior balance deficit were already active. Previous studies demonstrated a weak improvement in postural stability during stance in some CI patients postoperatively [Buchman et al, 2004;Parietti-Winkler et al, 2015;Shayman et al, 2017] where others have noted no change in the risk of falls based on similar measures to those we used [Louza et al, 2018]. Nonetheless, other authors have pointed out that in some patients a notable worsening took place after CI surgery [Holinski et al, 2012].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In contrast, those who would have been considered to be likely to have balance problems (those over 60 years of age and those with a balance deficit preoperatively) had no significant worsening in balance control, possibly because central compensation processes for the prior balance deficit were already active. Previous studies demonstrated a weak improvement in postural stability during stance in some CI patients postoperatively [Buchman et al, 2004;Parietti-Winkler et al, 2015;Shayman et al, 2017] where others have noted no change in the risk of falls based on similar measures to those we used [Louza et al, 2018]. Nonetheless, other authors have pointed out that in some patients a notable worsening took place after CI surgery [Holinski et al, 2012].…”
Section: Discussionsupporting
confidence: 49%
“…Some authors have suggested that an improvement in stance stability after fitting with a CI is due to improved auditory feedback [Parietti-Winkler et al, 2015;Shayman et al, 2017]. A similar improvement in stability was not observed for gait [Weaver et al, 2017].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thirteen studies calculated the unilateral weakness (UW) according to the Jongkees formula . Most studies defined UW > 20% to express hyporeflexia of the hSCC . Two studies referred to the side preponderance, and six studies based the assignment on the slow‐phase velocity, with a range of 3 ° to 20 ° per second as a cutoff value or unilateral weakness (Supporting Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory inputs provide additional cues to control balance, creating a hearing “map” of surroundings that NH individuals use to maintain balance control and reduce postural sway [16,22]. HI children may experience balance difficulties, especially those with vestibular deficits [23,24] or within the first year of cochlear implants, when children exhibit higher rates of vestibular loss [25,26,27,28]. Thus, HI children have shown lower stability limits, faster and higher body sway, and higher energy expenditure to keep balance than NH children, indicating a deficit in static and dynamic balance [14,26,29,30].…”
Section: Introductionmentioning
confidence: 99%